2007
DOI: 10.1117/12.704246
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effect of line profile variation on optical critical dimension metrology

Abstract: We investigate the effects that variations in profile have on specular and diffuse reflectance from a grating consisting of parallel lines. We investigate, as an example, a nominal grating consisting of photoresist or silicon lines on a silicon substrate, having a vertical sidewall angle, a width of 100 nm, a pitch of 200 nm, and a height of 200 nm. We model the effects of variations by calculating the reflectance of multiple 25-line superstructures, in which the positions of the line edges are randomly modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Work by Germer has investigated line edge and line width roughness in the long period regime and found that the results can be approximated by a incoherent average of line widths. 22,23 More recent results by Bergner, et al, investigated roughness in the short period regime and found that the results could be modeled with an effective medium layer, provided the layer was treated as a birefringent effective medium. 24…”
Section: Line Width/line Edge Roughnessmentioning
confidence: 96%
“…Work by Germer has investigated line edge and line width roughness in the long period regime and found that the results can be approximated by a incoherent average of line widths. 22,23 More recent results by Bergner, et al, investigated roughness in the short period regime and found that the results could be modeled with an effective medium layer, provided the layer was treated as a birefringent effective medium. 24…”
Section: Line Width/line Edge Roughnessmentioning
confidence: 96%
“…Quintanilha et al [26] presented an experimental study which yielded a negligible influence of LER on scatterometry measurements for the considered samples and tool configurations. Germer [27] investigated the effect of linewidth and line position variation from trench to trench, i.e. in the direction orthogonal to the lines.…”
Section: Introductionmentioning
confidence: 99%
“…Quintanilha et al [18] presented an experimental study which yielded a neghgible influence of LER on scatterometry measurements for the considered samples and tool configurations. Germer [19] investigated the effect of linewidth and line position variation from trench to trench, i.e. in the direction orthogonal to the hues.…”
Section: Introductionmentioning
confidence: 99%